Bioreactor-Grown Bacillus of Calmette and Guérin (BCG) Vaccine Protects Badgers against Virulent Mycobacterium bovis When Administered Orally: Identifying Limitations in Baited Vaccine Delivery - Sandrine Lesellier; Colin P. D. Birch; Dipesh Davé; Deanna Dalley; Sonya Gowtage; Simonette Palmer; Claire McKenna; Gareth A. Williams; Roland Ashford; Ute Weyer; Sarah Beatham; Julia Coats; et al. (MDPI AG, 2020)
Bovine tuberculosis (TB) in Great Britain adversely affects animal health and welfare and is a cause of considerable economic loss. The situation is exacerbated by European badgers (Meles meles) acting as a wildlife source of recurrent Mycobacterium bovis infection to cattle. Vaccination of badgers against TB is a possible means to reduce and control bovine TB. The delivery of vaccine in oral bait holds the best prospect for vaccinating badgers over a wide geographical area. There are practical limitations over the volume and concentration of Bacillus of Calmette and Guérin (BCG) that can be prepared for inclusion in bait. The production of BCG in a bioreactor may overcome these issues. We evaluated the efficacy of oral, bioreactor-grown BCG against experimental TB in badgers. We demonstrated repeatable protection through the direct administration of at least 2.0 × 108 colony forming units of BCG to the oral cavity, whereas vaccination via voluntary consumption of bait containing the same preparation of BCG did not result in demonstrable protection at the group-level, although a minority of badgers consuming bait showed immunological responses and protection after challenge equivalent to badgers receiving oral vaccine by direct administration. The need to deliver oral BCG in the context of a palatable and environmentally robust bait appears to introduce such variation in BCG delivery to sites of immune induction in the badger as to render experimental studies variable and inconsistent.